Complementarities between strategies to protect inventions and innovations: evidence from manufacturing SMEs. (6th February 2009) - Landry, Rejean; Amara, Nabil; Saihi, Malek
How should innovative firms manage the protection of their inventions and innovations from imitation when having to choose between various intellectual property protection methods? Data on manufacturing SMEs are used to investigate complementarities and independence between six protection mechanisms in order to see how they mix them to protect their technological innovations. The results of the study show that SMEs devise four generic protection strategies that are based on complementary mixes of mechanisms in order to protect their inventions and innovations. Moreover, the results also show that there are many important differences in the determinants of the different protection methods.